A multi-analytical protocol combining EDXRF, SEM+EDS, μXRD and Monte Carlo simulations applied to analyse non-destructively portuguese corroded copper coins - Diktas, Emine Guncem (2019)
Performing quantitative analyses on archaeological and cultural heritage metallic artefacts is challenging due to their complex multi-layered internal structure. “Layers” may include a) Original metal and/or alloy substrate (gold, silver, bronze etc.) b) Surface patinas enriched in corrosion products sulphides, oxides and/or chlorides compounds c) Protective treatments applied in past conservation interventions d) Soil derived incrustations from archaeological burial environment. To obtain compositional data on the metal substrate, usually these layers have to be removed but this not always possible due to the inherent fragility of the corroded artefacts as it is the case in particular with copper objects such as coins. The setting up of a non-destructive protocol is therefore important. In this study, a protocol combining SEM-EDS, μXRD, EDXRF and Monte Carlo simulations has been tested on a series of Portuguese coins from the 12th to the 19th centuries found at Largo das Olárias and Travessa do Jordão in Lisbon. 1. Analyze non-destructively the corrosion patterns and patinas developed on the surface Portuguese Copper coins from a Lisbon archaeological site (Largo das Olarias) SEM+EDS, μXRD and portable EDXRF 2. Apply the mineralogical and chemical data obtained during the analytical sessions to run Monte Carlo simulations of EDXRF spectra 3. Assess the feasibility of the combined non-destructive protocol in obtaining a reliable quantitative estimation of the metal substrate composition without the need to remove the surface corrosion patinas; RESUMO: Realizar análises quantitativas em artefactos metálicos arqueológicos de património cultural é um desafio devido à sua estrutura interna com múltiplas camadas. Essas ‘’Camadas’’ podem incluir: a) Substrato original de metal e / ou liga (ouro, prata, bronze etc.) b) Patinas de superfície enriquecidas em produtos de corrosão compostos de sulfetos, óxidos e / ou cloretos c) Tratamentos de protecção aplicados em intervenções de conservação passadas d) Incrustações derivadas do solo do ambiente de enterro arqueológico. Para obter dados de composição sobre o substrato metálico, geralmente essas camadas devem ser removidas, porém isso nem sempre é possível devido à fragilidade inerente aos artefactos corroídos, como é o caso em particular de objectos de cobre como as moedas. A criação de um protocolo não destrutivo é, portanto, importante. Neste estudo, um protocolo que combina as simulações SEM-EDS, μXRD, EDXRF e Monte Carlo foi testado numa série de moedas portuguesas dos séculos XII ao XIX encontradas num Largo das Olárias e Travessa do Jordão em Lisboa. 1. Analisar de forma não destrutiva os padrões de corrosão e patinas desenvolvidas na superfície de moedas de cobre portuguesas de um sítio arqueológico de Lisboa SEM + EDS, μXRD e EDXRF portátil. 2. Aplicar os dados mineralógicos e químicos obtidos durante as sessões analíticas para executar simulações Monte Carlo dos espectros EDXRF. 3. Avaliar a viabilidade do protocolo não destrutivo combinado na obtenção de uma estimativa quantitativa confiável da composição do substrato metálico sem a necessidade de remover as patinas de corrosão superficial.